L’economia occulta dei “soldi facili” tra i minatori di diamante della Sierra Leone - Lorenzo D'Angelo (EtnoAntropologia)
The idea of earning “easy money” is one of the reason that attracts diamond seekers in the mines of Sierra Leone. Only few miners, however, are successful and actually enrich themselves. In this paper I deal with the issue of how to make sense of those ritual practices and religious ideas that arise among miners to explain the wealth acquired by colleagues through non-trasparent and occult means.